Aplicação Web para consulta de cinemas: refinamento de buscas por cinemas na cidade de Osasco - NASCIMENTO, Diogo Borges; SANTOS, Felipe dos; REIS, Gustavo Antonio Pereira; SILVA, Otavio Heinrik da; BEZERRA, Francisco Sidenia Silva (143, 2021)
Na contramão da era de UX (User Experience), na qual o foco é otimizar a experiência do usuário na utilização de aplicações web ou mobile, alguns sites encontram-se repletos de informações irrelevantes que dificultam o acesso. Assim, este artigo sobre uma aplicação web para consultas de cinema da cidade de Osasco objetiva facilitar o acesso às informações sobre filmes e sessões bem como incentivar a ida ao cinema por meio de uma interface simples e intuitiva. Trata-se de uma pesquisa de caráter quali-quantitativo, inicialmente bibliográfica, com consulta a livros, artigos científicos, monografias, entre outros. A pesquisa surveys, teve como instrumento a observação direta e aplicação de questionários, os quais foram respondidos por cento e vinte usuários, por meio do Google Forms. A pesquisa revela que uma parcela considerável das pessoas utiliza plataformas digitais como fonte não somente de pesquisa, mas também para compra de seus ingressos.

Contrary to the UX (User Experience) era, where the focus is on optimizing the user experience when using web or mobile applications, some websites are filled with irrelevant information which makes access become difficult. Thus, this article about a web application for cinema consultations in the city of Osasco aims to facilitate access to information about films and sessions, as well as encourage going to the cinema through a simple and intuitive interface. Thus, this article about a web application for cinema consultations in the city of Osasco aims to facilitate access to information about films and sessions, as well as encourage going to the cinema through a simple and intuitive interface. It is qualitative-quantitative research, initially bibliographical, with consultation of books, scientific articles, monographs, and others. The survey research had as instrument the direct observation and application of questionnaires, which were answered by one hundred and twenty users, through Google Forms. The survey reveals that a considerable portion of people use digital platforms as a source not only for research, but also to purchase their tickets.
Web application for searching for cinemas: refining searches for cinemas in the city of Osasco
Keywords: Cinema; aplicativos móveis; Informação e Comunicação